Speculative music (2005)
Speculative music, or music theory with an esoteric base,has existed since ancient times in parallel with moremainstream aspects of music theory and musicology. Farfrom becoming extinct after the scientific revolution ofthe 16th and 17th centuries, speculative music has survivedmodernity, and recurs in times of cultural crises,repeatedly offering hopes of a spiritual and humanisticrenewal through the return to more “natural” forms ofmusic, closer to the physical and acoustical bases of soundthan the elaborate and “artificial” intellectual constructsdeveloped during “high modernism”. This article offers ageneral overview of this less known aspect of musicologyand musical theory, in its conceptual, historical, andcurrent aspects.